Factors effecting energy consumption of household refrigerator-freezers - Masjuki, Haji Hassan; Saidur, Rahman; Choudhury, I.A.; Mahlia, T.M.I. (2000)
An experiment was conducted to investigate the effect of temperature, door opening, thermostat setting position, relative humidity, and loading on energy consumption of a household refrigerator-freezer. Our investigation reveals that temperature has the greatest effect on energy consumption followed by loading. Next greatest effect are due to door opening and thermostat setting position. Relative humidity has minimal effect on energy consumption. With the experimental data, a multiple regression equation has been developed to investigate their combine effect.